Staged Hybrid Repair of a Complex Type B Aortic Dissection - Cristina-Maria Șulea; Csaba Csobay-Novák; Zoltán Oláh; Péter Banga; Zoltán Szeberin; Ádám Soltész; Zsófia Jokkel; Kálmán Benke; Máté Csonka; Eperke Dóra Merkel; Béla Merkely; Zoltán Szabolcs; et al. (Journal of Cardiovascular Development and Disease, 2022)
Due to its heterogeneous clinical picture and lengthy evolution, the management of type B aortic dissection represents a clinical challenge, often calling for complex strategies combining medical, endovascular, and open surgical strategies. We present the case of a 45-year-old female who had previously suffered a complicated type B aortic dissection requiring a femoro-femoral crossover bypass and further conservative treatment. Seven years later, due to an aneurysmal development, a staged descending aortic management was strategized, beginning with the implantation of a frozen elephant trunk device due to an insufficient proximal landing zone for endovascular repair. However, the development of a distal stent graft-induced new entry complicated the dissection and led to the formation of a second false lumen, thus prompting an expedited hybrid reconstruction. We describe a hybrid repair strategy tailored to the patient’s particular aortic anatomic conformation, combining ilio-visceral debranching and thoracic endovascular aortic repair. Due to a lack of consensus on the ideal management strategy for type B aortic dissection, an individualized approach conducted by an experienced aortic team may generate the best outcome. The appropriate timing and planning of the intervention are the keys to successful results in complex type B aortic dissection cases with an elaborate anatomic conformation.